COMPATIBILITY OF LAW ENFORCEMENT AND HUMAN RIGHTS WITHIN ISLAMIC LAW IN ACEH PROVINCE, INDONESIA - Gani, Iskandar A. (Kanun Jurnal Ilmu Hukum, 2024)
Since the enactment of Act Number 11 of 2006 on the Governance of Aceh, the region has undergone decentralization, becoming an asymmetrical area with unique authority, particularly in the realm of Islamic Law. The implementation of Islamic law in Aceh has encountered obstacles and sparked debates among scholars. This article delves into the enforcement of Islamic laws and their relationship with human rights within the context of Aceh Province. Through doctrinal legal research, it is demonstrated that the enforcement of Sharia Law in Aceh upholds human rights principles. The justification for Islamic Sharia law is rooted in the Indonesian Constitution of 1945, provided that Qanuns (sub-national regulations) at the provincial or regional level align with higher laws hierarchically. Any discrepancies in implementation necessitate a reevaluation. The 1945 Constitution grants Aceh the authority to uphold Islamic law while promoting, respecting, and fulfilling human rights. The harmonization of human rights and Islamic Law is crucial for mutual reinforcement and justice-seeking in Aceh Province, Indonesia.